Blind Photographers: Vision, Accessibility, and Empowerment in the Museum - McCulloh, Douglas (Disability Studies Quarterly, 2013)
Photographs by blind artists are inherently conceptual. They operate at the heart of the medium, questioning the nature of sight and blindness, perception and photography. This paper uses a traveling museum exhibition—Sight Unseen: International Photography by Blind Artists—as a case study to explore these ideas and their implications for disability activism and exhibition accessibility. Using concrete examples and approaches, the paper proposes that an exhibition of work by blind photographers should become a laboratory of perception. The paper concludes that the goal of exhibition design and interpretive elements should not be one-sided—access for the blind. Rather it should be reciprocal—equalizing the status of the blind and sighted. Such an exhibition accords the blind the right to fully inhabit and display the products of their rich visualizations, while impelling the sighted to question the scope and reliability of their own vision. Key Words: Blind access to museums, blind photographers, accessible curatorial practices.